PERENCANAAN GEDUNG PERKULIAHAN 3 LANTAI DENGAN PONDASI SARANG LABA-LABA DI UNIVERSITAS TIMOR (TTU) - Wilfridus Palbeno; Nawir Rasidi; Galih Damar Pandulu (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2018)
University of Timor is one of the educational institutions located in Central Timor Regency (NTT) and very important role in improving human resources. In this thesis, taking the topic of planning the building on the foundation of the cobwebs. The foundation cobweb is a combination of conventional substructure which is a blend of flat concrete slab foundation constantly filled with soil improvement so that it becomes an integral composite reinforced concrete. These systems are specifically use the land as part of the foundation structure. This study aims to determine the strength of the foundation ksll meet q_a(Raft Foundation) < q_a(Foundations KSLL) and the cost required. The parameters used are from the test results sondir. The analysis starts from determining soil classification and load analysis. Then calculate the bearing capacity of the foundation, the maximum ground voltage, decrease, equivalent thickness, reinforcement dimensions ksll and budget plan (RAB) In University Timor East Timor Regency North. The results of the analysis of the maximum loading of 306.465 tons. Calculation of ground voltage due to the load of the building q = 5.352 tons / m². Calculation of the effective soil pressures (po) = 3.5022 or at 35.022 kn / m². Calculation of reduction / settlement total is 1.99 cm. Equivalent thickness of rib construction / settlement t_e = 134.5 cm. High-rib construction / settlement is 1.70 m. While the load distribution rib area construction / settlement is 5.81 t / m². Control of the shear reinforcement rib construction is s